rancang Bangun Aplikasi Pendeteksi Bentuk Dan Warna Benda Pada Mobile Robot Berbasis Webcam - Pancasila Prayitno, Yustinus; Harianto, Harianto; Christrian W., Madha (Journal JCONES, 2012)
Robotino is an omni-directional drive robot created by Festo Didatic and has integrated a variety of sensors and a webcam in it. By utilizing Computer Vision, Robotino can be used as a ball-detection robot based on shape and color of objects. Commonly, RGB color space are used while the process of color segmentation, but the RGB color space still unable to tolerate the intensity of light. In this project has been build an application using the HSV color space for color filtering process which is able to tolerate the intensity of light in image processing and the methods for detect a circle is using Circular Hough Transform. Moreover, in this study the image data obtained directly via webcam on Robotino streamingly. This application has been successfully detected the colored balls with the parameters specified filter color in HSV color space and the Circular Hough Transform method, as well as the processed image data obtained through wireless,streamingly fromRobotino’s webcam which is already integrated on the PC. Keywords: Robotino, HSV Color Filtering, Circular hough transform, Streaming